2014
DOI: 10.1002/adma.201400158
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Theranostic Red Blood Cells For Magnetic‐Field‐Enhanced in vivo Combination Therapy of Cancer

Abstract: Red blood cells are attached to iron oxide nanoparticles pre-coated with chlorine e6, a photosensitizer, and then loaded with a chemotherapeutic drug, doxorubicin, to enable imaging-guided combined photodynamic and chemotherapy of cancer, achieving excellent synergistic therapeutic effects in an animal tumor model. This work highlights the great promise of integrating cell-based drug-delivery systems with nanotechnology as a biocompatible multifunctional platform for applications in cancer theranostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 38 publications
(41 reference statements)
2
151
0
Order By: Relevance
“…83 However, for further clinical applications of this approach, it is also necessary to evaluate the long-term toxicity of these decoy particles, in addition to all other concerns related to safety of the IONPs. As an alternative approach, Wang et al 84 labeled red blood cells with IONPs and observed a significantly longer blood circulation time and efficient tumor targeting after intravenous administration of these cells.…”
Section: Ionps Pharmacokineticsmentioning
confidence: 99%
“…83 However, for further clinical applications of this approach, it is also necessary to evaluate the long-term toxicity of these decoy particles, in addition to all other concerns related to safety of the IONPs. As an alternative approach, Wang et al 84 labeled red blood cells with IONPs and observed a significantly longer blood circulation time and efficient tumor targeting after intravenous administration of these cells.…”
Section: Ionps Pharmacokineticsmentioning
confidence: 99%
“…Therefore, the elevation of ROS around tumor environment can selectively kill cancer cells. Photodynamic therapy has been successfully used in skin diseases in the clinic and further extended to cancers 30-33. ROS produced by photosensitizers can be used in photodynamic therapy and to cleave thioketal groups to release drugs.…”
Section: Introductionmentioning
confidence: 99%
“…With appropriate targeting ligands and surface modifications, an enhanced accumulation of IONPs in tumor tissues by passive or active targeting has been shown in animal tumor models while significantly reducing nonspecific accumulation in the liver and spleen [29,30]. Moreover, the unique magnetic properties of IONPs offer strong MRI contrast enhancing effect for MRI to monitor of drug delivery, evaluate treatment responses and external magnetic-field-controlled drug release or hyperthermia treatment [31]. Therefore, IONP is an excellent candidate for the development of new tumor imaging, targeted drug delivery and image-guided therapy that have the potential for novel clinical applications.…”
mentioning
confidence: 99%